2000
DOI: 10.1007/s101890070028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal undulations on the bending elasticity and spontaneous curvature of fluid membranes

Abstract: We amplify previous arguments why mean curvature should be used as measure of integration in calculating the effective bending rigidity of fluid membranes subjected to a weak background curvature. The stiffening of the membrane by its fluctuations, recently derived for spherical shapes, is recovered for cylindrical curvature. Employing curvilinear coordinates, we then discuss stiffening for arbitrary shapes, confirm that the elastic modulus of Gaussian curvature is not renormalized in the presence of fluctuati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 15 publications
2
42
1
Order By: Relevance
“…This is not quite as clear for the membrane as for the polymer since a cap representing local mean curvature is accompanied by a brim of saddle curvatures which, however, are fully slaved. In calculations of the effective bending rigidity it has been shown that normal displacement is insufficient as statistical measure if membrane or polymer are subjected to a background curvature [10]. In the present article normal displacement fails as measure (or is at least impractical) for other reasons.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…This is not quite as clear for the membrane as for the polymer since a cap representing local mean curvature is accompanied by a brim of saddle curvatures which, however, are fully slaved. In calculations of the effective bending rigidity it has been shown that normal displacement is insufficient as statistical measure if membrane or polymer are subjected to a background curvature [10]. In the present article normal displacement fails as measure (or is at least impractical) for other reasons.…”
Section: Discussionmentioning
confidence: 66%
“…It is automatically used in Monte Carlo simulations. For the nearly flat membrane without background curvature, one-dimensional normal displacement (Du) is good enough and results, in fact, in the same configurational statistics as mean curvature (DJ), as was discussed in detail elsewhere [10]. Like bend in the case of polymers, mean curvature may be called the natural measure because it is identical to the relevant strain, i.e.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Conflicting values for the prefactor—α = 1 [51, 56, 57], α = 3 [5254] and α = −1 [58, 59]—pointing to both thermal softening (α = 1 and 3) and stiffening (α = −1) have been reported. In spite of these contradictions, it should be remembered that we measure κ R from experiments and molecular simulations, whereas we impose κ in mesoscale/continuum simulations based on the Helfrich energy functional.…”
Section: Thermodynamics-based Models For Membranesmentioning
confidence: 99%